2021
DOI: 10.3390/nu13103481
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Normobaric Hypoxia Combined with a Mixed Diet Contributes to Improvement in Lipid Profile in Trained Cyclists

Abstract: This study aimed to analyze the effects of live high-train low method (LH-TL) and intermittent hypoxic training (IHT) with a controlled mixed diet on lipid profile in cyclists. Thirty trained male cyclists at a national level with at least six years of training experience participated in the study. The LH-TL group was exposed to hypoxia (FiO2 = 16.5%) for 11–12 h a day and trained under normoxia for 3 weeks. In the IHT group, participants followed the IHT routine three times a week under hypoxia (FiO2 = 16.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Moreover, we unexpectedly found that visceral fat mass was significantly lowered, indicating that IHT may be helpful to alleviate visceral obesity and further reduce visceral-obesity-related mortality and morbidity [ 3 , 35 ]. Some clinical trials also found that IHT has a positive effect on lipid profiles, and subjects of the IHT group tend to have increased high-density lipoprotein cholesterol levels and decreased total cholesterol, low-density lipoprotein cholesterol, and triglycerides [ 36 ]. However, our results did not show significant changes in lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we unexpectedly found that visceral fat mass was significantly lowered, indicating that IHT may be helpful to alleviate visceral obesity and further reduce visceral-obesity-related mortality and morbidity [ 3 , 35 ]. Some clinical trials also found that IHT has a positive effect on lipid profiles, and subjects of the IHT group tend to have increased high-density lipoprotein cholesterol levels and decreased total cholesterol, low-density lipoprotein cholesterol, and triglycerides [ 36 ]. However, our results did not show significant changes in lipid profiles.…”
Section: Discussionmentioning
confidence: 99%